Alcohol and oesophageal cancer: an assessment of the evidence from routinely collected data. Issue 2 (June 1979) - Chilvers, C; Fraser, P; Beral, V
Abstract : Although various factors have been implicated in the aetiology of oesophageal cancer, one factor common to many countries is the consumption of alcoholic beverages. In England and Wales mrtality from oesophageal cancer declined rapidly during the early part of this century but both mortality and incidence have increased in recent years. The generation of males born in 1906 had lower mortality than any preceding or succeeding generation. It is suggested that ages 20 to 30 may be critical in the development of oesophageal cancer and that the 1906 cohort was less exposed to alcohol than other generations. The international analysis suggests that ethyl alcohol itself rather than any specific alcoholic beverage is associated with this cancer.